Development of the falls risk for older people in the community (FROP-Com) screening tool - Russell, M.; Hill, Keith; Day, L.; Blackberry, I.; Gurrin, L.; Dharmage, S. (Oxford University Press, 2009)
Background: The aim of this study was to develop a brief screening tool for use in the emergency department (ED), to identify people who require further assessment and management. Methods: This prospective study included 344 community-dwelling older people presenting to an ED after a fall. After direct discharge participants had a home-based assessment performed that included the Falls Risk for Older People in the Community (FROP-Com), a comprehensive, yet simple, multifactorial falls risk assessment tool. They were then monitored for falls for 12 months. The items from the FROP-Com assessment tool predictive of falls in a multifactorial logistic regression were used to develop the FROP-Com screen. Results: The items significantly predictive of falls and combined to form the FROP-Com screen were: Falls in the previous 12 months, observation of the person's balance and the need for assistance to perform domestic activities of daily living. At the cut-off with the highest Youden index sensitivity was 67.1% (95% CI 59.9-74.3) and specificity was 66.7% (95% CI 59.8-73.6). Conclusion: the FROP-Com screen has a relatively good capacity to predict falls. It can be used in time-limited situations to classify those at high risk of falls who require more detailed assessment and management. © The Author 2009. Published by Oxford University Press on behalf of the British Geriatrics Society. All rights reserved.